Antimicrobial Drimane Sesquiterpenes Contribute to Balanced Antagonism but Do Not Structure Bacterial and Fungal Endophytes in the African Pepper Bark Tree Warburgia ugandensis - Drage, Sigrid; Mitter, Birgit; Engelmeier, Doris; Chobot, Vladimir; Gorfer, Markus; Muchugi, Alice; Jamnadass, Ramni H.; Sessitsch, Angela; Hadacek, Franz (Frontiers in Ecology and Evolution, 2017)
The African pepper bark tree, Warburgia ugandensis, accumulates antimicrobial drimane sesquiterpenes in all of its organs. One hypothesis states that plant defense compounds determine endophyte community structure. Another hypothesis suggests that they just facilitate the endophytic lifestyle by exerting a balanced antagonism. To explore this, a representative selection of endophytic bacterial and fungal isolates from this tree species was assayed together with six non-endophytic strains to determine their tolerance and susceptibility to the root and leaf extract fraction containing high and low drimane sesquiterpene amounts respectively. Inhibitory effects were explored by assessing both growth and growth efficiency, the latter of which relates respiratory activity to growth. The susceptibility of the tested strains showed considerable variation and the obtained patterns did not allow a clear distinction between root and leaf endophytes as well as endophytes and non-endophytes. In addition, all strains were also assayed against juglone, an antimicrobial and redox-active aromatic naphthoquinone. A comparison of differential pulse voltammograms and efficacy in variants of the deoxyribose degradation assay revealed that drimane sesquiterpenes possess anti- and pro-oxidant activities that compare to those of juglone. Leaf endophytes showed higher resistance to oxidative stress than root endophytes, quite contrary to the actual exposure. The obtained results support the notion that structural diverse plant defense compounds can contribute to a balanced antagonism against but not to structuring of endophyte communities. Oxidative stress seems to be involved in generating this effect albeit it cannot explain it alone.